The Influences of Director’s Remuneration, Earnings Management and Ownership Structure on Company Performance: Before and During the Covid-19 Pandemic - Komang Ayusta Devi Savitri; I G.A.M Asri Dwija Putri (Universitas Pendidikan Ganesha, 2023)
Company performance is a measure of company management's achievement in utilizing company’s financial resources. Besides showing the effectiveness of asset management, good performance reflects stable profitability. Covid-19 pandemic has decreased the revenues gained by companies of various sectors, resulting in lower company performance. To maintain their sustainability, some internal policies were implemented, by taking into account some factors that can affect company performance which include remuneration of directors, earnings management, managerial ownership, and institutional ownership. Eight transportation companies listed on the Indonesia Stock Exchange for the 2018-2021 period were purposively selected as samples based on the predetermined criteria. 32 observations were performed to investigate the influences of director’s remuneration, earnings management, managerial ownership and institutional ownership on company performance. After that, the gaps in company performance before and during the Covid-19 pandemic were also analyzed. The results showed that director’s remuneration negatively affected the company performance. Furthermore, earnings management and managerial ownership have a positive effect on company performance, and institutional ownership has no effect on company performance.